A randomized controlled study of immediate versus delayed umbilical cord clamping in infants born by elective caesarean section - Giuseppe De Bernardo; Maurizio Giordano; Rita De Santis; Paola Castelli; Desiree Sordino; Daniele Trevisanuto; Giuseppe Buonocore; Serafina Perrone (BMC, 2020)
Abstract Background Delayed umbilical cord clamping is associated with greater haemoglobin concentration and iron storage between 3 and 6 months of life and with less need of blood transfusion and lower incidence of neonatal hypotension compared to early umbilical cord clamping. Methods The aim was to test the hypothesis that delayed cord clamping is better than early cord clamping in term infants born by elective caesarean section. Group A was subjected to immediate cord clamping while in the Group B, the umbilical cord was clamped 1 min after birth. Primary aim was revealed the difference in pre-ductal saturation between two groups while secondary aim was investigating the difference in HR, Ht, bilirubin and glycaemia. Pre-ductal SpO2 and HR were recorded at 5 and 10 min after birth, T was analysed 10 min after birth, glycaemia was revealed at 120 min while Ht and bilirubin were collected at 72 h. Results 132 newborns were enrolled in the study and allocated in ratio 1:1 to group A or B. Delayed cord clamping did not improve SpO2, HR and T values compared to immediate cord clamping (p > 0,05). However, Group B showed greater haematocrit and bilirubin values at 72 h compared to Group A (56,71 ± 6663 vs 51,56 ± 6929; p < 0,05 and 8,54 ± 2,90 vs 7,06 ± 2,76; p < 0,05). Glycaemia value did not differ between two groups (p > 0,05). Conclusions Group B did not reveal any differences in SpO2, HR, T and glycaemia compared to Group A. Group B showed greater values of haematocrit and bilirubin but without need of phototherapy. Trial registration Umbilical Cord Clamping: What Are the Benefits; NCT03878602 . Registered 18 March 2019 retrospectively registered.